An ever more critical dialogue: Table‐talking with Paulo Freire on education and liberation. Issue 2 (26th April 2022) - Brondos, David A.
Abstract: This past year marked the centenary of the birth of Brazilian educator Paulo Freire (1921–1997). Like Martin Luther, Freire saw literacy, critical reflection, and dialogue among those oppressed by systems that exploited and excluded them as the primary means toward their liberation. As we seek to address systemic injustice and oppression today, we can learn a great deal by looking to the pedagogical thought of Freire and Luther and placing them in critical dialogue with one another and with our own contexts.